ANALISIS PENGEMBANGAN KEMAMPUAN MEMBACA PADA SISWA KELAS II DI SD MUHAMMADIYAH 1 BONTOALA - Irmayanti, leni Irmayanti; Hastati, Sri; Nurdiansyah, Erwin; Prabu Setiawan, Ince; Nasaruddin, Nasaruddin (ALENA : Journal of Elementary Education, 2023)
Abstract. Education has an important role in improving human resources, with education it can provide various kinds of changes, including changes in individual social strata as access to education must be equal and equitable. The Covid-19 pandemic that hit various countries including Indonesia has changed the way we do our daily activities. In the post-COVID-19 pandemic, the state of education in Indonesia still needs to be considered considering that 2 years of students studying at home independently without direct interaction with teachers. Teaching Campus 3 is presented to enable students to take part in helping improve literacy and numeracy in schools, adapting technology and assisting school administration. This study aims to (1) determine the reading ability of second grade students at SD Muhammadiyah 1 Bontoala. (2) knowing the development of reading skills in class II students at SD Muhammadiyah 1 Bontoala. The subjects in this study were class II homeroom teachers and class II students. The data collection instrument is the researcher himself by means of interviews, observation, and documentation. The results showed that the application of a culture of reading to reading skills in students experienced significant progress, this can be seen from the indicators in reading ability, namely: students recognize letters and read them as syllables, words, and simple sentences, read aloud (heard by other students ) sentence by sentence with paragraphs and use the correct pronunciation and intonation, and read short texts with the correct pronunciation and intonation.